Formation of Psychological and Pedagogical Problems Through Sports Motivation - Khatamov Zafarjon Nazirjonovich (European Science Publishing, 2023)
High results in sports are closely related to a person's motivational field. Motivation is not only the main feature of the athlete's personality, which leads him to the goal, but also affects the nature of all processes that occur in the body during the activity. The main feature of sports motivation is its direct impact on the athlete's performance. In the face of fierce competition, only a motivated athlete with the maximum intensity of motivation can be expected to give full dedication and desire to win. Underestimating the role of motivational factors, taking into account the dynamics of motivation changes by sports teachers, coaches and athletes themselves, often leads to a person not being able to demonstrate his potential, to realize the great work he did while playing sports.
Keywords: motive, sports motivation, sports activity, personal characteristics, level of demands.